A Study on Designing the Identity of a Product - Huang-Chen Lu; Ming-Chyuan Ho (Journal of ICT, Design, Engineering and Technological Science, 2017)
This study aims to explore how enterprise designers use their techniques to shape identity products that can be linked with the brand efficiently to fill in the hole in this area. This study uses qualitative research to analyze and interpret the thesis data. The literature research, content analysis method, in-depth interview method and focus group method are used to compare and summarize the data and construct with rooted theory. We found that we can shape the identity product by designing the identity product through specific rules. Product identity consists of product composing factors and product shaping factors. Only when we develop key product identifying features and characteristics of the group can our products be recognized, on which the strategic thinking elements to identify the product are based. An amalgamation of these factors while designing the product will help in creating products that are alluring for customers, beneficial for brands and profitable for the business.